Iatrogenic Extra-Capsular Extension of Knee Septic Arthritis Via Intra-Articular Joint Injection - Nawaf Al-saeed; Ahmed Altayeb; Saud Alawad; Steven Mosey (Journal of Sports and Exercise Medicine, 2025)
Background Septic arthritis is a potentially limb or life-threatening joint infection that requires prompt recognition and intervention to reduce morbidity and mortality. While intra-articular joint injections are commonly performed for osteoarthritis and other arthropathies, they carry a rare but significant risk of iatrogenic infection, particularly when performed in the presence of unrecognized joint or periarticular infection. Case Presentation We report a case of a 52-year-old female with a history of traumatic brain injury and chronic right knee pain who developed severe knee swelling, pain, and systemic symptoms following an intra-articular corticosteroid injection performed without ultrasound evaluation/guidance. Post-procedure, she presented with fever, elevated inflammatory markers, and purulent knee effusion. Operative washout revealed a purulent tract extending from the knee joint capsule to the lateral thigh. Cultures from joint aspiration and intraoperative samples grew Streptococcus dysgalactiae. Blood cultures were negative. The patient reported frequent cat scratches to the affected knee and described an unusual sensation of the injection needle tracking laterally during the joint injection. She was treated with surgical drainage and a four-week course of amoxicillin, with full clinical recovery. Discussion This case highlights an unusual presentation of septic arthritis with extra-capsular extension likely due to iatrogenic needle tracking during joint injection. The causative organism, S. dysgalactiae, is an uncommon pathogen in septic arthritis, and the presumed source was contiguous spread from untreated cellulitis, possibly related to cat scratches/bites. The absence of predisposing comorbidities and negative blood cultures further support a local rather than hematogenous source. The case emphasizes the importance of thorough clinical evaluation and consideration of infection prior to joint injections, as well as the potential benefits of ultrasound guidance to minimize procedural complications. Conclusion Careful history, physical examination, and appropriate imaging are essential prior to joint interventions to avoid iatrogenic complications. This case illustrates the rare but serious risk of extra-capsular extension of septic arthritis following intra-articular injection and emphasizes the need for vigilance in identifying underlying infection before proceeding with invasive procedures.
Keywords: Injection